Konsep Kecakapan Subjek Hukum Dalam Kewenangan Bertindak Pada Hukum Perkawinan Di Indonesia Dari Perspektif Psikologis - Martinelli, Imelda; Priyono, Joko; Yunanto, Yunanto (Jurnal Hukum & Pembangunan, 2023)
This study explores the concept of 'injustice' in legal policy, focusing on the 'criterion of injustice' from the perspective of the individual's legal rights. The study identifies several differences in Indonesian legal systems, but focuses on the 'injustice' principle as a common principle in the legal system. The study also discusses the concept of 'injustice' as a legal principle that can be applied both in the public and private sectors. The study also highlights the role of 'law' in legal policy, which is a central aspect of legal research and is still present in the legal system. The study distinguishes between two main groups of law: law as a branch of legal discipline and law as an activity of obtaining ‘values'. The methodology used in this writing is a legal normative method. The study concludes that 'law' is a political activity that aims to achieve a specific social goal as a result of its principles. Psychological theories suggest a significant difference between 18 and 19-year-olds, with 19-year-olds often being considered as a priority due to the shorter school year in Indonesia, although the answer for this due to the conditions, 18-year-olds is considered a proper marriageable age.